Exploring the Need for Research Data Management Services: A Study of CSIR Laboratories in India - Zhimomi, Alovi; Rath, Durga Sankar (DESIDOC Journal of Library & Information Technology, 2025)
The realisation of Findable, Accessible, Interoperable, and Reusable (FAIR) research data principles is contingent upon proper Research Data Management (RDM) practices by the researchers who generate data. Accordingly, it is pertinent to investigate how they manage their research data and gain insight into researchers’ need for RDM support service. This study explores the nature of research data generated by researchers, their perception of RDM and their needs for library services. An online survey comprising 48 questions was administered to researchers at the Council of Scientific & Industrial Research (CSIR) laboratories, yielding 173 complete responses. The survey findings indicate that there are significant gaps in RDM awareness and practice: 97 % has limited knowledge of RDM, the majority are not aware of FAIR data principles (74 %) and 71 % lack knowledge of metadata. The results also reveal differences in research data across domains, indicating the need for tailored data management approaches. Despite the knowledge gaps, there is high level of willingness among researchers to share research data (86 %), keenness to receive training on research data management (98 %), and interest in availing research data services if offered by the library. This study concludes that researchers currently lack the necessary knowledge and skills for effective data management and there is a need for libraries to take a forefront role as facilitators of research data management services.